Digital Democracy: Freedom and Permissive in Digital Citizenship - Utami, Wahyu Kartiko (International Journal of Demos (IJD), 2025)
Democracy is not a sure thing. It always has dynamics movement, where today, democracy has been transformed into digital democracy, and on the other hand, citizens have been transformed into digital citizens usually called netizens. With the internet, the way of communication among citizens, states, and even social organizations has changed. It is clear that many citizens of this digital age have demonstrated interest in making a contribution to society. However, not all citizens can participate in digital democracy as well as digital citizenship. This study used qualitative research methods and the approach used in this research is descriptive research. Data were collected through observation and documentation. The result of this study is that there are still obstacles and challenges, especially for young people to participate in digital democracy. One of the obstacles and also challenges for digital citizens is freedom in digital democracy. Permissive on the other hand also becomes one great obstacle for digital citizens to explore social media and make a contribution to digital democracy. Citizens, an especially young citizen is active player in society, both in the future and in the present, so that their ideas, values, and contributions can influence democracy as well as digital democracy. Unfortunately, young citizens become one of the players that often face the issue of freedom or permissive in digital democracy.